Where Does Politics Shape the Individual? Trust in Science and Scientists across Political Regimes and Educational Cohorts before and during Covid-19 - Savostianov,Artem (2026)
The thesis explores the associative patterns between trust in science and scientists and political regimes across different educational groups in pre- and intra-pandemic periods. Using a multilevel design with regression-based methods on the sample (N = 168,035 two survey waves) with observations from 110 countries, I find that the relationship between political regime and trust in science is educational-cohort- specific. Among the least educated, trust decreases as the regimes move away from the most authoritarian end of the political spectrum and then stagnates. In the secondary cohort, a U-shaped relationship is observed. Trust in science and scientists among individuals with higher education does not show a statistically meaningful association with political regime. The present study employs an eclectic interpretation framework, which consists of Legitimization and Merton’s theories, supplemented by literature-based insights, to suggest an explanation for the observed patterns. The findings suggest that the association between democratization and trust is nonlinear and can involve both declining and increasing trust depending on whether democratization is partial or fully-fledged, and on the educational group in question. During the Covid-19 period, trust generally increased across all educational cohorts in autocracies, while in democratic contexts, the increase was concentrated among the tertiary-educated. In democratic contexts, policies aimed at promoting science during the pandemic may have led to a decrease rather than an increase in trust among the less educated.
Keywords: trust; science; scientists; political regime; education